Progress in the use of microemulsions for transdermal and dermal drug delivery. (19th May 2017) - Ita, Kevin
Abstract: Transdermal drug delivery continues to attract considerable interest in the scientific community. However, due to the hindrance provided by the stratum corneum, it is not possible to deliver most medications in therapeutically significant amounts. One of the ways of increasing the penetration of drugs across the skin is through the use of microemulsions (MEs). This review focuses on the role of MEs in enhancing topical and transdermal drug delivery.